2016
DOI: 10.3109/03639045.2016.1141931
|View full text |Cite
|
Sign up to set email alerts
|

Development, optimization, and characterization of a novel tea tree oil nanogel using response surface methodology

Abstract: TTO EG turned out to be a promising vehicle for the topical delivery of TTO with enhanced therapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…TTO incorporated in nanocapsules has been reported in the literature [13][14][15]. However, the major drawbacks of the reported formulations are the presence of harsh solvents and chemicals that could potentially cause adverse effects, which is consistent with the USP <467> requirements [14,16].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…TTO incorporated in nanocapsules has been reported in the literature [13][14][15]. However, the major drawbacks of the reported formulations are the presence of harsh solvents and chemicals that could potentially cause adverse effects, which is consistent with the USP <467> requirements [14,16].…”
Section: Introductionmentioning
confidence: 59%
“…However, the major drawbacks of the reported formulations are the presence of harsh solvents and chemicals that could potentially cause adverse effects, which is consistent with the USP <467> requirements [14,16]. Furthermore, the existing research uses the concentration of excipients beyond the limit specified by regulatory agencies such as US Food and Drug Administration for topical use [13][14][15]. Thus, the commercial translation of other reported topical formulations loaded with TTO is not possible [14,15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the nanoemulsions successfully facilitated the delivery of the extract through the SC. In addition, the hydrophilic part of nanoemulsions can hydrate the SC probably facilitating skin uptake of the compound [40]. Our findings suggested that the evolved nanoemulsions could successfully improve stability and skin permeability of M. indica kernel extract, which might provide better outcomes for topical anti-acne applications.…”
Section: Discussionmentioning
confidence: 75%
“…To the best of the authorsʼ knowledge, only a few studies are available on TTO permeation [11][12][13], with all of them investigating markers accumulated in the skin by solvent extraction. In 2006, Reichling et al [7] compared several formulations and studied the permeation of the major TTO component, i.e., 4-terpineol, without measuring its distribution in the skin layers.…”
Section: Melaleuca Alternifolia Essential Oil: Evaluation Of Skin Permentioning
confidence: 99%